Group Formation Techniques in Computer-Supported Collaborative Learning: A Systematic Literature Review - Maqtary, Naseebah; Mohsen, Abdulqader; Bechkoum, Kamal (Springer Nature, 2019)
Group formation is an essential process for group development lifecycle. It has been a growing concern to many researchers to be applied automatically in collaborative learning contexts. Forming a group is an atomic process that is affected by various factors. These factors differ depending on the group members characteristics, the context of the grouping process and the techniques used to form the group(s). This paper surveys the recently published work in group formation process providing a systematic literature review in which 30 relevant studies were analyzed. The findings of this review propose two taxonomies. The first one is for the attributes of group formation while the second is for the grouping techniques. Furthermore, we present the main findings and highlight the limitations of existing approaches in computer supported collaborative learning environment. We suggest some potential directions for future research with group formation process in both theoretical and practical aspects. In addition, We emphasize other improvements that may be inter-related with other computing areas such as cloud computing and mobility.